Effects of social participation and physical activity on all-cause mortality among older adults in Norfolk, England: an investigation of the EPIC-Norfolk study. (January 2022) - Fain, R.S.; Hayat, S.A.; Luben, R.; Abdul Pari, A.A.; Yip, J.L.Y.
Abstract: Objectives: There is growing evidence of an association between social participation and improved physical and mental health among older individuals. The aims of this study were to explore the relationship between self-reported participation in groups, clubs, or organizations and all-cause mortality among older adults and examine the role of physical activity as a potential modifier of the health effects of social participation. Study design: EPIC-Norfolk is a prospective cohort study that recruited 25, 639 individuals between the ages of 40 and 79 in Norfolk County, England. This study involved a retrospective analysis of 8623 participants who had returned for the third health check between 2004 and 2011. Methods: Participants were categorized into those who reported participating socially and those who did not and were stratified by involvement in 0, 1, or 2 or more groups. Cox Proportional Hazards models were constructed to compare all-cause mortality between the groups. Stratum-specific hazard ratios were calculated by physical activity level to assess for effect modification. Results: Of the participants, 861 (9.98%) died during the follow-up period. After adjustment for confounding, social participation was associated with lower all-cause mortality (HR 0.84, 95% CI 0.73–0.97). Involvement in 2 or more groups was associated with lower all-cause mortality (hazard ratio [HR] 0.83, 95% confidence interval [CI] 0.70–0.97), but the association was not statistically significant for people involved in only 1 group (HR 0.86, 95% CI 0.73–1.03). Physical activity appeared to modify the effect of social participation on mortality. Conclusions: This study's findings provide evidence of an association between social participation and lower all-cause mortality for older adults. They also suggest that the effect of social participation on health is greater for people who are more physically active. Population-level interventions to facilitate social participation may contribute to improving health and wellbeing among older individuals.